Pengembangan Desa Wisata Terhadap Kesejahteraan Masyarakat Desa Penglipuran, Kecamatan Bangli, Kabupaten Bangli - Sutanegara Bagiana, I Gusti Bagus Yogi; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 9. September 2017(pp.1628-1867), 2017)
Tourism is one of sectors which contribute dominant on economic growth. District bangli having tourist village that was popular which is a penglipuran village. Visitors to the penglipuran in 2015 down so the visits to the penglipuran have an impact on employment opportunities and public welfare. The research was conducted in penglipuran villages using data primary with of respondents about 69 families. The purpose of this research to analyze the tourist rural development, tourist visits in welfare through employment opportunities in the village penglipuran using path analysis. The result showed that the rural development tourism and tourist visits influential positive and significantly to employment opportunities. Tourist rural development, tourist visits and employment opportunities influential positive and significant in public welfare and employment opportunities as variable mediation relations tourism rural development and tourist visits significant in public welfare.   Keywords: tourist rural development, tourist visits, employment opportunities, public welfare